Crucial Role of Legionella pneumophila TolC in the Inhibition of Cellular Trafficking in the Protistan Host Paramecium tetraurelia - Nishida, Takashi; Hara, Naho; Watanabe, Kenta; Shimizu, Takashi; Fujishima, Masahiro; Watarai, Masahisa (Frontiers in Microbiology, 2018)
Legionella pneumophila is a facultative intracellular gram-negative bacterium, which is a major causative agent of Legionnaires’ disease. In the environment, this bacterium survives in free-living protists such as amoebae and Tetrahymena. The association of L. pneumophila and protists leads to the replication and spread of this bacterium. Thus, from a public health perspective, their association can enhance the risk of L. pneumophila infection for humans. Paramecium spp. are candidates of natural hosts of L. pneumophila, but their detailed relationships remain unclear. In the present study, we used an environmental strain, L. pneumophila Ofk308 (Ofk308) and P. tetraurelia st110-1a to reveal the relationship between L. pneumophila and Paramecium spp. Ofk308 was cytotoxic to P. tetraurelia in a multiplicity of infection-dependent manner. We focused on TolC, a component of the type I secretion system, which is a virulence factor of L. pneumophila toward protists and found that cytotoxicity was dependent on TolC but not on other T1SS components. Further, the number of bacteria in P. tetraurelia was not associated with cytotoxicity and TolC was not involved in the mechanism of resistance against the digestion of P. tetraurelia in Ofk308. We used a LysoTracker to evaluate the maturation process of P. tetraurelia phagosomes containing Ofk308. We found that there was no difference between Ofk308 and the tolC-deletion mutant. To assess the phagocytic activity of P. tetraurelia, Texas Red-conjugated dextran-uptake assay was performed. Ofk308 inhibited phagosome formation by P. tetraurelia through a TolC-dependent mechanism. Further, we evaluated the excretion of Legionella-containing vacuoles from P. tetraurelia. We found that P. tetraurelia failed to excrete undigested Ofk308 and that Ofk308 remained within cells through a TolC-dependent mechanism. Our results suggest that TolC is essential for L. pneumophila to remain within Paramecium cells and to show cytotoxicity. Because of the high mobility and high cell division rate of Paramecium spp., living with Paramecium spp. would be beneficial for L. pneumophila to expand its habitat. To control Legionaries’ disease, understanding the ecology of L. pneumophila in the environment is essential.